Multiple bottom line reporting - Juico, Philip Ella (Animo Repository, 2007)
Corporate social responsibility (CSR) is a term coined by Andrew Carnegie a hundred years ago. It is an old concept whose time has come. Today engaging in CSR is a badge of corporate citizenship. CSR involves the management of three aspects: the economic, which involves the study of the implications of resource consumption; the ecological, particularly in regard to energy use and its effects - not to mention the effects of a firm's entire operation on environmental integrity; and finally the social, which is about maximizing the positive impacts of a firm's operations on broader social concerns like public health, social justice, etc. The ability of a company to maintain and pursue activities in these areas is called sustainability development, which is encapsulized in a term coined by John Eklington's sometime in the mid 1990s - Triple Bottom Line Reporting or TBL. The TBL evolved from the traditional bottom line, - primarily net income, to a double bottom line, which includes the legal and political aspects of corporate reporting. The double bottom line reporting itself has metamorphosed into John Eklington's TBL, a concept fast gaining acceptance in Europe, Australia, New Zealand, and even India. Its evolution is expected to continue to give birth to a quadruple bottom line, which takes ethics into account - how business is conducted both within and outside the organization. It will not be surprising if a quintuple bottom line develops one that concerns itself with the health of employees considerably. This initiative is expected to translate to reduced absenteeism and increased productivity. This will cover not only the physical fitness but also the emotional, social, spiritual, and intellectual well-being of employees. Indeed, as society and industry become more complex and competitive, a multiple bottom line may be adopted - one that addresses such other human concerns as cultural, spiritual, and familial ones. Any discussion of multiple bottom line reporting necessitates a brief review of CSR. According to Annette Tomal, assistant professor in the Business and Economics Department of Wheaton College, CSR may be defined as an action a firm chooses to take that substantially affects an identifiable social stakeholder's welfare (William and Siegel, 2001, as cited by Itkomen). Carroll (1979) says Mcguire and Backman have expanded this definition by saying it is a corporate practice that not only include economic and legal considerations but also goes beyond them. The modern definition of CSR is the pursuit of profit within the context of at least three areas (for the time being) taken all together- economic, social, and environmental development.